2006
DOI: 10.1097/01.prs.0000195080.65662.f5
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Wounds Closed under a Significant Amount of Tension

Abstract: This study demonstrates the considerable difference in scar formation among scalp, back, and shoulder defects compared with those on the extremities, groin, and thigh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Except for the prospective research of Daya and Nair on traction-assisted dermatogenesis for large scar excisions, which works by biological creep, no other techniques are available that showed a benefit for reducing a multistep procedure to a one-step procedure. 33 In a previously published article by Melis et al, the wounds closed with a skin-stretching device measured 5.6 ϫ 9.6 cm (n ϭ 28), 22 whereas the wounds in our skin stretch study group measured 8.8 ϫ 23.5 cm. Although the mean size of our wounds was considerably larger, one should note that different selection criteria were applied.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Except for the prospective research of Daya and Nair on traction-assisted dermatogenesis for large scar excisions, which works by biological creep, no other techniques are available that showed a benefit for reducing a multistep procedure to a one-step procedure. 33 In a previously published article by Melis et al, the wounds closed with a skin-stretching device measured 5.6 ϫ 9.6 cm (n ϭ 28), 22 whereas the wounds in our skin stretch study group measured 8.8 ϫ 23.5 cm. Although the mean size of our wounds was considerably larger, one should note that different selection criteria were applied.…”
Section: Discussionmentioning
confidence: 98%
“…22 In this study, the mean width of the wound was 56.4 Ϯ 19.2 mm and the mean reduction of the surface area was 72.9 Ϯ 25.5 percent. The clinical intended effect for this randomized controlled trial was a scar reduction of at least 50 percent.…”
Section: Power Analysis and Statisticsmentioning
confidence: 98%
See 2 more Smart Citations
“…By applying intermittent and controlled load of 30 Newton on the wound edges, tissue can be gained without compromising blood supply and the quality of the skin. In a clinical study Melis et al demonstrated that, even though wounds were closed under a significant amount of tension, a relatively narrow scar was achieved and a low incidence of hypertrophic scarring (7.1%) [28]. In a randomised controlled trial Verhaegen et al studied the effectiveness of wound closure with a skin stretching device [27].…”
Section: Tissue Expansionmentioning
confidence: 98%